2018
DOI: 10.1177/1076029618792304
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Concentration Affects Fibrin Clot Structure and Morphology as Evidenced by Fluorescence Imaging and Molecular Simulations

Abstract: Although in vivo studies have been conducted in the past to determine hyperglycemic effects and influence on clotting risk in patients with diabetes, the true extent of hyperglycemia on unstable and spontaneous clot formation remains highly debated. Factors such as increased glycation, elevated fibrinogen concentration, elevated prothrombin levels, and decreased plasminogen are known to influence fibrin conversion, clot morphology, and thrombus formation in these individuals. In this regard, the isolated effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
0
14
0
3
Order By: Relevance
“…Additionally, only a slight insignificant reduction of V max was observed for the glucose-incubated fibrinogen when glucose was absent during polymerization, compared to control fibrinogen not subjected to the influence of glucose. Hood et al have reported a reduced fiber overlap in a fibrin subjected to glucose, decreased fibrin length and fractal dimension, and increased porosity of fibrin incubated in media containing 10 mM glucose compared to glucose-free control media [ 18 ]. Native fibrinogen was incubated with glucose (6 or 10 mM) for 48 h, following which, a fibrin clot was polymerized in the presence of glucose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, only a slight insignificant reduction of V max was observed for the glucose-incubated fibrinogen when glucose was absent during polymerization, compared to control fibrinogen not subjected to the influence of glucose. Hood et al have reported a reduced fiber overlap in a fibrin subjected to glucose, decreased fibrin length and fractal dimension, and increased porosity of fibrin incubated in media containing 10 mM glucose compared to glucose-free control media [ 18 ]. Native fibrinogen was incubated with glucose (6 or 10 mM) for 48 h, following which, a fibrin clot was polymerized in the presence of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of glucose incorporation into fibrinogen, determined as the difference between glucose concentrations recorded for time 0 and time 48 h, was found to be the highest under the hyperglycemic condition. Molecular docking and molecular dynamics simulation suggest that glucose adsorption on fibrinogen is highly dependent on the glucose concentration and characterized by a high affinity of glucose molecule to the hydrophobic amino residues [ 18 ]. In addition, Lippi et al have note that fibrinogen concentration measured by the Clauss method significantly decreased with increasing glucose contamination (0–5–10–20%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Строение и свойства тромба являются важными детерминантами болезней и смертности, связанных с сердечно-сосудистой патологией [1][2][3][4][5][6][7]. Одним из основных факторов, определяющих характеристики тромба, являются изменения в молекуле фибриногена, которые могут влиять на скорость гемокоагуляции, структуру фибринового матрикса и его восприимчивость к фибринолизу [1,[8][9].…”
Section: Introductionunclassified
“…However, often there arises a problem which needs customized molecular simulations. This can be due to the boundary condition, the construction of the system itself, approximate models for introducing new force fields (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) or can be coupling between different time or length scales. To account these studies, graduate students often write their own code which is a cumbersome task (20,21,28).…”
Section: Introductionmentioning
confidence: 99%